Analisis Hubungan DPRD Dan Pemerintah Kota Palangka Raya Pada Penyusunan Dan Penetapan Peraturan Tentang APBD - Nurhasanah Nurhasanah; Nenie Adriati Lambung (Pencerah Publik, 2018)
The purpose of this study is to describe and analyze the relationship between the DPRD and the City Government of Palangka Raya in the preparation and determination of the Regional Budget and to describe and analyze the factors that influence the relationship between the DPRD and the City Government of Palangka Raya in the preparation and stipulation of APBD regulations. This study uses descriptive qualitative research methods. The types and sources of data chosen by researchers are primary data and secondary data. Data collection techniques used to obtain information are interviews and documentation. The results showed that the pattern of interaction between the executive and the legislature in the discussion of the Regional Expenditure Budget (APBD) in Palangka Raya City in 2018, starting from the stages of KUA and PPAS formulation and the RAPBD discussion until the budget approval stage was always colored by several phenomena of interaction between the executive and legislative to carry out the functions of authority to master each other, dominate. In determining budget policy, it was found that the relationship between the DPRD and the City Government of Palangka Raya in the preparation and stipulation of the Regional Budget was still conducive so that it did not lead to deadlock in the formulation and determination of the Palangka Raya City Budget in 2018. Factors affecting the interaction of DPRD and Palangka City Government Raya in the preparation and determination of APBD is the existence of a special mission to negotiate in the form of non-agenda, bargaining with executives to gain the interests of the legislature, a vision that may be different in running a good governance (transparent, democratic, good, fair, responsible and objective ) and equalize the same understanding in responding to every issue and scene in formulating local regulations on APBD and their implementation.